2020
DOI: 10.3390/nu12010126
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep Quality and Macronutrient Distribution: A Systematic Review and Meta-Regression

Abstract: Sleep is involved in metabolic, emotional and cognitive regulation and is therefore an essential part of our health. Although an association between sleep quality and macronutrient intake has been reported, studies on the effect of macronutrient distribution with sleep quality are limited, and available results are inconsistent. In this study, we aim to assess the association between sleep quality and macronutrient distribution in healthy adults from systematically reviewed cross-sectional studies and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…In a sleep intervention study, St-Onge et al [43] found that higher saturated fat and carbohydrate intake was associated with lighter sleep profile and more nocturnal sleep arousals, respectively. In a systematic review, people who slept poorly were observed to have a diet with a higher caloric contribution of carbohydrates and fats when compared to those who slept well [45]. We observed a high carbohydrate consumption among our subjects with a lower prevalence of poor sleep quality; however, this consumption was associated with a higher intake of fiber, vitamins, and minerals, and thereby justifies the positive impact of this macronutrient on sleep quality.…”
Section: Discussionmentioning
confidence: 47%
“…In a sleep intervention study, St-Onge et al [43] found that higher saturated fat and carbohydrate intake was associated with lighter sleep profile and more nocturnal sleep arousals, respectively. In a systematic review, people who slept poorly were observed to have a diet with a higher caloric contribution of carbohydrates and fats when compared to those who slept well [45]. We observed a high carbohydrate consumption among our subjects with a lower prevalence of poor sleep quality; however, this consumption was associated with a higher intake of fiber, vitamins, and minerals, and thereby justifies the positive impact of this macronutrient on sleep quality.…”
Section: Discussionmentioning
confidence: 47%
“…St‐Onge et al 28 observed similar effects of CHO manipulation on sleep compared to ours; namely, CHO manipulation influenced sleep architecture, but the review did not distinguish acute vs long term manipulation. Sutano et al 29 concluded that good sleepers consumed more energy from protein and less from fat and carbohydrate compared to poor sleepers. Given the differences in approach, all of the reviews provide meaningful analyses of the diet‐sleep literature.…”
Section: Discussionmentioning
confidence: 99%
“…25 The present review excludes supplements due to the fact that minimal monitoring of supplements occurs in the United States and promoting their use could be unsafe in some cases. 26,27 Other reviews either did not include comparison groups 28 or included observational studies in their analyses, 22,29,30 which precludes discussions of causality. Still others included individuals suffering from various conditions that could serve as a confounding variable to both sleep and diet [31][32][33][34] ; therefore, it can be argued that clinical populations should be studied separately.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been shown that foods rich in melatonin (a sleep promoting hormone), or its precursors tryptophan and serotonin, micronutrients (vitamin D and B, magnesium, zinc), carbohydrate-containing foods, food items including cherries and fish, can improve sleep parameters (e.g., sleep latency, time, efficiency). Contrarily, caffeinated and sugar-rich beverages as well as high fat (mainly saturated fat) and processed foods may negatively affect sleep quality and duration [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%